PEDOT-PSS embedded comb copolymer membranes with improved CO2 capture - Lee, Jae Hun; Jung, Jung Pyo; Jang, Eunji; Lee, Ki Bong; Hwang, Yun Jeong; Min, Byoung Koun; Kim, Jong Hak (ELSEVIER SCIENCE BV, 2016)
Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT-PSS) is a widely used conductive polymer in various electronic devices. Here we report the first use of PEDOT-PSS to enhance CO2 capture performance of all-polymeric membranes. Specifically, an amphiphilic comb copolymer, i.e. poly(2-[-3(2H-benzotriazol-2-yl)-4-hydroxyphenyll ethyl methacrylate)-poly(oxyethylene methacrylate) (PBEMPOEM or PBE), was synthesized to disperse PEDOT-PSS chains. Isolated and aggregated PEDOT-PSS transformed into an interconnected network structure upon combination with PBE, due to specific interactions. Incorporation of PEDOT-PSS generated a facile pathway for enhanced diffusive transport, resulting in improved CO2 and N-2 permeability. However, CO2 permeability increased more significantly due to enhanced CO2 solubility, resulting in slight increase in CO2/N-2 selectivity. The PBE membrane containing PEDOT-PSS 5 wt% showed the highest performance with a CO2 permeability of 59.6 Barrer and CO2/N-2 selectivity of 77.4. The performance of PBE/PEDOT-PSS membranes was very close to the 2008 Robeson upper bound and much higher than those of PBE/PEDOT, PBE/PSS and commercial PEBAX membranes. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: MIXED-MATRIX MEMBRANES; GAS SEPARATION PROPERTIES; ORGANIC FRAMEWORK; COMPOSITE MEMBRANES; PERFORMANCE; SELECTIVITY; ADSORPTION; POLYIMIDE; PEG